Prescription pattern of antibiotics in neonatal intensive care unit of tertiary care hospital - Baig, Shiraz Mirza; Naikwadi, Imran B.; Deshmukh, L. S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Recurrent and prolonged courses of antibiotics exposure have resulted in an increase in the prevalence of hospital acquired infections and antibiotic resistant profile. The objective of this study was to quantify the use of antibiotics in a neonatal intensive care unit (NICU) of Govt. Medical College and Hospital, Aurangabad, Maharashtra, a tertiary health care centre. Methods: A total of 260 neonates admitted in NICU from August 2017 to February 2018 were enrolled in the study and fulfilling inclusion criteria of the study. Demographic details, data on antibiotic prescriptions (name, dose, frequency, route of administration) was recorded on pre-tested structured Performa. Results: A total of 248 neonates received the antibiotics. EOS pneumonia was most common i.e. 29.8% followed by LOS pneumonia (20.6%). Sepsis, pneumonia Meningitis, NEC, were common indications for admission in NICU. Among the antibiotic combinations amoxicillin + clavulanate (38.99%), was most commonly prescribed followed by gentamicin (37.89%) and piperacillin (11.01%) respectively. Other antibiotics like, linezolide (0.94%), fluconazole (5.97%), meropenem (4.42%), vancomycine (0.77%) were also used less commonly in NICU. About fifty of the medicine prescribed were in compliance with the national list of essential medicines 2011. Conclusions: In tertiary care setup of NICU amoxicillin + clavulanate and gentamicin are most commonly used antibiotics in NICU. The study concludes that the antibiotic prescription pattern at NICU of our tertiary care hospital was found rational.